Analisis Pengaruh Brand Image, Kualitas Produk dan Harga Terhadap Volume Penjualan Produk Perum Bulog - Hafiz Akbar; Veny Puspita; Idham Lakoni (Journal of Trends Economics and Accounting Research, 2023)
Perum Bulog is one of the BUMNs whose job is to manage food ingredients. Different sales quality of course has a different price. This of course will affect sales volume because people's interest is different for each food product that is sold. The purpose of this study was to analyze the effect of brand image, product quality and price on sales volume of Bulog Perum products in Bengkulu City. This research was carried out by applying quantitative methods with an associative approach. The research population is all consumers at Perum Bulog Bengkulu City with a total sample of 90 respondents. Determination of the sample in this study using a purposive sampling technique. The data analysis used is multiple linear regression and the coefficient of determination (R2). The hypothesis testing in this study uses the T test and F test. The results show that based on the results of the T test Variable X1 (Brand Image) and X2 (Product Quality) on Y (Sales Volume) have a significant value ≤ 0.05, this means X1 and X2 have a significant effect on Y, meanwhile the variable X3 (price) on Y (sales volume) has a significant value ≥ 0.05, this means that X3 has no significant effect on Y. The results of the f test between Variables X1 (Brand Image), X2 (Product Quality) and X3 (Price) on Y (Sales Volume) have a significant value ≥ 0.05, this means that X1, X2 and X3 have no significant effect on Y.